CRITICAL EVALUATION OF THE ISLAMIC RELIGIOUS EDUCATION ASSESSMENT SYSTEM: A QUALITATIVE STUDY IN THE ERA OF THE INDEPENDENT CURRICULUM - Gusti Muhammad Alfarizi; Salamah (International Journal of Multidisciplinary Reseach, 2025)
This research aims to critically evaluate the assessment system in Islamic Religious Education (PAI) learning in the era of the Independent Curriculum with a qualitative approach. The focus of the study lies in how teachers apply assessment principles in the cognitive, affective, and psychomotor domains, as well as the extent to which the evaluation system used is able to represent the achievement of students' competencies holistically. Data were obtained through in-depth interviews, classroom observations, and documentation at several junior high schools in a given region. The results of the study show that there is still a gap between the ideal concept of assessment mandated in the Independent Curriculum and real practice in the field. Teachers tend to emphasize the cognitive aspect more and ignore the assessment of students' attitudes and spirituality. In addition, the lack of teacher training and understanding of holistic evaluation instruments is the main obstacle in the development of a comprehensive assessment system. This study recommends the need to improve teachers' competence in designing evaluation instruments that are contextual and in accordance with the characteristics of Islamic Religious Education.